Using data to improve outcomes of supplemental immunisation activities: 2017/2018 Nigeria measles vaccination campaign. (17th November 2021) - Mogekwu, Fred Ikechukwu; Oteri, Joseph A; Nsubuga, Peter; Ezebilo, Obiora; Maxwell, Nikki; Wiwa, Owens; Braka, Fiona; Shuaib, Faisal
Abstract: Background: Despite the enormous resources committed to the implementation of supplemental immunisation activities in Nigeria, achieving the required coverage (post-campaign survey) to halt the transmission of vaccine-preventable diseases has continued to seem like an impossibility. A vast volume of data is generated and transmitted during mass vaccination campaigns, but this administrative data does not always culminate into improved coverage. The absence of data-informed guidance from stakeholders with long years of experience in planning and implementing mass vaccination campaigns has impeded achieving 95% coverage in measles campaigns in Nigeria. This study reviews the use of data to guide the implementation of the 2017/2018 measles vaccination campaign in Nigeria. Methods: A central coordinating body was formed at the national level with the same replicated in every state. Tools were developed to measure the performance of the different phases and activities required for the implementation of a mass vaccination campaign as recommended in the international guidelines. Stakeholders were engaged to help ensure that feedback provided by the national measles technical coordinating committee was implemented at the lower level. Results: Monitoring and analysis of daily data submission caused a proper spread of senior supervisors, vaccination posts location during the campaign and helped identify areas targeted for mop-up. Although the verification of states' microplan increased the operational target population by 11.2%, the process aided the distribution of resources as appropriate. Maps showing the likely areas that needed additional effort to achieve required coverage with recommendation on the necessary approach to be deployed were transmitted to the states implementing the campaign. Conclusion: The improvement in the use of data to guide implementation of the Nigeria 2017/2018 measles vaccination campaign caused an increase in the number of states that achieved higher coverage in the post-campaign coverage survey.